2018
DOI: 10.1111/jce.13445
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of left ventricular dyssynchrony by three‐dimensional echocardiography: Prognostic value in patients undergoing cardiac resynchronization therapy

Abstract: SDI is independently associated with long-term prognosis after CRT and might therefore be important to optimize risk-stratification in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Our results are based on the study of a contemporary international multicenter population receiving standard state of the art contemporary heart failure therapy, and are comparable in terms of outcome with other heart failure similar populations who received CRT. 19,[32][33][34] Thus, our results represent international, multicenter, diverse populations, which reflects everyday clinical practice across these developing countries. Moreover, the software analysis of gSPECT MPI was totally automated and done by a central core lab, and electrophysiologists were not aware of the gSPECT MPI results.…”
Section: Strengths Of the Vision-crt Studymentioning
confidence: 92%
“…Our results are based on the study of a contemporary international multicenter population receiving standard state of the art contemporary heart failure therapy, and are comparable in terms of outcome with other heart failure similar populations who received CRT. 19,[32][33][34] Thus, our results represent international, multicenter, diverse populations, which reflects everyday clinical practice across these developing countries. Moreover, the software analysis of gSPECT MPI was totally automated and done by a central core lab, and electrophysiologists were not aware of the gSPECT MPI results.…”
Section: Strengths Of the Vision-crt Studymentioning
confidence: 92%
“…Recently, the calculation of the systolic dyssynchrony index (SDI) via real-time 3D echocardiography showed a superiority in the assessment of LV performance following CRT [68]. In contrast to a previous small study which reported that CRT optimization of interventricular delay by using SDI (vs. QRS width) assessment did not reveal any significant difference in terms of volumetric and clinical response at the 12-month follow-up [69], recent large studies have demonstrated that a more pronounced reduction in SDI immediately after CRT is independently associated with a superior long-term outcome [70], and that SDI derived by 3D speckle-area tracking shows a good correlation with the reduction of end-systolic volume post-CRT [71]. However, there is no consensus regarding the feasibility of using SDI to optimize the CRT.…”
Section: Mechanical Workmentioning
confidence: 59%
“…[11][12][13] Advances in automated software technology will further promote its use into daily clinical practice as it allows rapid analysis of five representative beats, improving LV volumes and EF accuracy and reproducibility in these patients ( Figure 5). [14][15][16][17][18] 19,20 One caveat to the reporting of 3DE LV volumes is that currently there are no age-or gender-specific reference ranges for interpretation. Previous studies have produced promising values in large cohorts; however, these are population specific and have been based on healthy subjects.…”
Section: Valid It Y Of 3de For a Ss E Ss Ment Of Lef T Ventri Cul Amentioning
confidence: 99%